Measuring the Project Management Complexity: The Case of Information Technology Projects - Rocio Poveda-Bautista; Jose-Antonio Diego-Mas; Diego Leon-Medina (Complexity)
Complex projects require specific project management (PM) competences development. However, while no complex projects have standards that are recognized to guide their management, complex projects do not have guides to deal with their complexity. To lead complex projects to success, this complexity must be measured quantitatively and, in our opinion, project management complexity assessment should be based on existing PM standards. In this work, the main project complexity assessment approaches based on PM standards are analyzed, observing that International Project Management Association (IPMA) approach is the closest to a tool that can be used as a complexity quantitative measurement system. On the other hand, several authors have shown that the inherent complexity of specific kind of projects must be measured in a particular way. The main objective of this research is to propose a project management complexity assessment tool for IT projects, providing a Complexity Index that measures the impact that complexity factors inherent to IT projects have under a specific complexity scenario. The tool combines the use of complexity factors defined by IPMA approach and the use of complexity factors found in the literature to manage inherent complexity of IT projects. All these factors were validated by expert survey and the tool was applied to a study case.